Simple Coaching Clinic to Improve Nurse's Knowledge of Genetic Counseling among Thalassemia Patients - Firmansyah, Andan; Yuda, Hendri Tamara; Putri, Tri Antika Rizki Kusuma; Hidayat, Nur; Richard, Selvia David; Arifin, Hidayat; Setiawan, Henri (Genius Journal, 2024)
Introduction: The coaching clinic is one of the strategies designed to increase nurses' knowledge in conducting genetic counseling for patients and families of thalassemia patients. Nurses will not only be given information, but they will also be taught how to communicate and how to use genetic counseling to make sure the coaching clinic's goals are met. Objective: This study aims to describes the effect of a simple coaching clinic on nurses' knowledge of genetic counseling implementation in thalassemia care. Methods: This research used a quantitative approach and was conducted on August 20th–21st , 2022. The design of this study was quasi-experimental without a control group. This study obtained a total sample of 29 nurses using a proportional sampling technique and inclusion criteria. The inclusion criteria in this study were nurses with a diploma degree, an undergraduate education background, and registered nurses. The data collection instrument was a 30-questions genetic counseling questionnaire. IBM SPSS version 25.0 was used to analyze the data using the Wilcoxon test. Results: Simple coaching clinic proved to have a significant effect in improving the knowledge level of nurses in general with p-value = 0.004. Knowledge level improvement can be seen from Mean (+SD) 53.67 (+13.64) to 69.67 (+8.26). Likewise with nurses' knowledge about thalassemia, genetic counseling and bio-informatics, the majority of respondents experienced positive changes. In contrast to the genetic topic, the majority of respondents did not experience a change in their level of knowledge so that a p-value >0.05 was obtained. Conclusions: Changes in level of knowledge indicated that the coaching clinic's effects on level of knowledge are significant and have an impact on health services across a variety of health institutions, including clinics and hospitals. As a result, it is critical to have a health strategy that promotes the accessibility of genetic counseling services for patients with thalassemia and other genetic illnesses.